Alterations of irisin concentrations in saliva and serum of obese and normal-weight subjects, before and after 45 min of a Turkish bath or running - Aydin, Suleyman; Aydin, Suna; Kuloglu, Tuncay; Yilmaz, Musa; Kalayci, Mehmet; Sahin, Ibrahim; Cicek, Demet (Elsevier Science Inc, 2013)
The purpose of this study was to ascertain (1) whether human saliva contains irisin and whether its level correlates with serum irisin concentration, (2) whether salivary glands, eccrine glands and sebaceous glands in human skin produce irisin, (3) how the changes in saliva and serum irisin concentrations after the Turkish bath at 47 + 3 degrees C compare with the changes caused by moderate exercise in obese and normal weight subjects. Seven obese male subjects and seven normal weight subjects were enrolled for Turkish bath. Seven obese male subjects and seven normal weight subjects were also enrolled for moderate outdoor exercise, and thirteen male normal weight subjects neither exercised nor showered at the Turkish bath. From each participant, 1.5 ml of saliva and 5 ml blood were collected simultaneously before and after the moderate exercise and Turkish bath. Salivary glands and eccrine and sebaceous glands in the skin were screened immunohistochemically for irisin while serum and saliva irisin were measured with an ELISA. Submandibular glands, eccrine glands and sebaceous glands in the human skin showed strong irisin immunoreactivity. Human saliva contained irisin and its level was significantly higher than the serum levels in both obese and normal weight subjects. However, irisin concentrations were more markedly increased in both saliva and serum samples from subjects who had showered at a Turkish bath than in obese subjects who had exercised or in normal weight subjects. Human submandibular glands, eccrine sweat glands and sebaceous glands synthesize irisin. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Irisin; Saliva; Serum; Obesity; Turkish bath; Exercise